Altered Transcriptional Control Networks with Trans-Differentiation of Isogenic Mutant-KRas NSCLC Models - Haley, John A.; Haughney, Elizabeth; Ullman, Erica; Bean, James; Haley, John D.; Fink, Marc Y. (Frontiers in Oncology, 2014)
Background The capacity of cancer cells to undergo epithelial mesenchymal trans-differentiation has been implicated as a factor driving metastasis, through the acquisition of enhanced migratory/invasive cell programs and the engagement of anti-apoptotic mechanisms promoting drug and radiation resistance. Our aim was to define molecular signaling changes associated with mesenchymal trans-differentiation in two KRas mutant NSCLC models. We focused on central transcription and epigenetic regulators predicted to be important for mesenchymal cell survival. Experimental design We have modeled trans-differentiation and cancer stemness in inducible isogenic mutant KRas H358 and A549 non-small cell lung cell backgrounds. We employed large-scale quantitative phospho-proteomic, proteomic, protein-protein interaction, RNA-Seq and network function prediction approaches to dissect the molecular events associated with the establishment and maintenance of the mesenchymal state. Results Gene set enrichment and pathway prediction indicated BMI1, KDM5B, RUNX2, MYC/MAX, NFkB, LEF1, and HIF1 target networks were significantly enriched in the trans-differentiation of H358 and A549 NSCLC models. Physical overlaps between multiple networks implicate NR4A1 as an overlapping control between TCF and NFkB pathways. Enrichment correlations also indicated marked decrease in cell cycling, which occurred early in the EMT process. RNA abundance time course studies also indicated early expression of epigenetic and chromatin regulators, including CITED4, RUNX3, CMBX1 and SIRT4. Conclusions Multiple transcription and epigenetic pathways where altered between epithelial and mesenchymal tumor cell states, notably the polycomb repressive complex-1, HP1g and BAF/Swi-Snf. Network analysis suggests redundancy in the activation and inhibition of pathway regulators, notably factors controlling epithelial cell state.